Global Gene Expression of T Cells Is Differentially Regulated by Peritoneal Dendritic Cell Subsets in an IL-2 Dependent Manner - Sohn, Moah; Na, Hye Young; Shin, Hyun Soo; Ryu, Seul Hye; Park, Sejung; In, Hyunju; Choi, Wanho; Park, Ji Soo; Hwang, Soomin; Chu, Min Kyung; Park, Chae Gyu (Frontiers in Immunology, 2021)
Dendritic cells (DCs) in peripheral tissues may have a unique role to regulate innate and adaptive immune responses to antigens that enter the tissues. Peritoneal cavity is the body compartment surrounding various tissues and organs and housing diverse immune cells. Here, we investigated the specialized features of classical DC (cDC) subsets following the intraperitoneal injection of a model antigen ovalbumin (OVA). Peritoneal cDC1s were superior to cDC2s in activating OVA-specific CD8 T cells, while both cDCs were similar in stimulating OVA-specific CD4 T cells. Each peritoneal cDC subset differentially regulated the homing properties of CD8 T cells. CD8 T cells stimulated by cDC1s displayed a higher level of lung-homing receptor CCR4, whereas those stimulated by cDC2s prominently expressed various homing receptors including gut-homing molecules CCR9 and α4β7. Also, we found that cDC1s played a dominating role over cDC2s in controlling the overall gene expression of CD8 T cells. Soluble factor(s) emanating from CD8 T cells stimulated by peritoneal cDC1s were responsible for mediating this dominance of cDC1s, and we identified IL-2 as a soluble factor regulating the global gene expression of T cells. Collectively, our study indicates that different peritoneal cDC subsets effectively diversify T cell responses by altering the level of cytokines, such as IL-2, in the milieu.